Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan di Bengkel PT. Dunia Barusa Meulaboh - Mahzalena, Rahmi; Yusnaidi, Yusnaidi (Regress: Journal of Economics & Management, 2023)
This article aims to analyze the effect of service quality on customer satisfaction in PT. New World Meulaboh. Service quality is a major basis for determining the level of customer satisfaction. This study aims to determine the effect of service quality on customer satisfaction at PT. Dunia Barusa Meulaboh workshop. This study uses simple linear regression using primary and secondary data. This sampling technique uses accidental sampling. The results of this study show that the simple linear regression equation shows that service quality affects the level of customer satisfaction at PT.Dunia Barusa Meulaboh Workshop. Therefore, companies need to continue to strive to improve service quality so that customers are more satisfied.